Fotografia e processos criativos : três poéticas contemporâneas em Manaus - Tavares, Khetllen da Costa (2016)
This research aims to contribute to the study of contemporary photography produced in Manaus, to reflect on the creative process of the photographic image, through the productions of Carlos Navarro, Raphael Alves, Ricardo Oliveira that permeated the photo club environment during their careers. These selected according to originality, production time, relevant work, public recognition, participation in local, national and international exhibitions, recurring names in events targeting the public fond of photography in Manaus. It is believed that this study contributes to understanding of photography beyond the technical or aesthetic aspect, and emphasizes the discourse triggered by the photographer and the reality in which developed the record. Therefore, the investigation was executed from iconographic analysis of each author's essay, Urban Decay by Navarro, Riversick by Alves, Rubber tappers: Roads of life by Oliveira, in order to observe expression, creative process and aesthetic dialogues. As the theoretical basis, it was based on the studies of Philippe Dubois, Boris Kossoy, Susan Sontag, André Rouillé, Joan Fontcuberta, Annateresa Fabris, Helouise Costa, Renato Rodrigues, Rubens Fernandes Jr. and Katia Canton. Ahead, the methodology consisted of mapping the local photo clubs, developing interview scripts, cataloging the collection of photographers participants, development of iconographic analysis and the realization of an audiovisual product with artistic works and the photographers participants. At the end, there was the presence of memory, dialogue and direction in the work of Carlos Navarro, Raphael Alves and Ricardo Oliveira, respectively, as it was found in the study compared with consolidated production in the national art scene, the presence of resonances of modernity intertwined with the contemporary. However, it emphasizes the breadth of the subject, then open to other viewpoints, in order to foster more research in this field. Keywords: Photo clubs; Creative process; Contemporary art; City